2013
DOI: 10.1158/0008-5472.can-13-0657
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific Antibody to ErbB2 Overcomes Trastuzumab Resistance through Comprehensive Blockade of ErbB2 Heterodimerization

Abstract: The anti-ErbB2 antibody trastuzumab has shown significant clinical benefits in metastatic breast cancer. However, resistance to trastuzumab is common. Heterodimerization between ErbB2 and other ErbBs may redundantly trigger cell proliferation signals and confer trastuzumab resistance. Here, we developed a bispecific anti-ErbB2 antibody using trastuzumab and pertuzumab, another ErbB2-specific humanized antibody that binds to a distinct epitope from trastuzumab. This bispecific antibody, denoted as TP L , retain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 44 publications
3
49
1
Order By: Relevance
“…A variety of compensatory mechanisms may underlie acquired resistance to EGFR-or HER2-targeted agents, including switching dimerization partners (7), upregulation of ligands for HER3 or EGFR (24,26,41), or overexpression of particular receptors, especially HER3, which are identified as an evolved response to current anti-HER/ErbB agents needing early and direct blockade (42). In a previous study, a bispecific antibody generated from trastuzumab and pertuzumab also supported this hypothesis, overcoming acquired resistance to trastuzumab by effectively blocking HER2/HER3 heterodimerization (19). Moreover, receptor crosstalk of MET plays a critical role in the development of resistance to EGFR family inhibitors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A variety of compensatory mechanisms may underlie acquired resistance to EGFR-or HER2-targeted agents, including switching dimerization partners (7), upregulation of ligands for HER3 or EGFR (24,26,41), or overexpression of particular receptors, especially HER3, which are identified as an evolved response to current anti-HER/ErbB agents needing early and direct blockade (42). In a previous study, a bispecific antibody generated from trastuzumab and pertuzumab also supported this hypothesis, overcoming acquired resistance to trastuzumab by effectively blocking HER2/HER3 heterodimerization (19). Moreover, receptor crosstalk of MET plays a critical role in the development of resistance to EGFR family inhibitors.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, in 2009, catumaxomab (Removab, Neovii Biotech) was approved as the first bispecific antibody drug for the treatment of malignant ascites (18). For anti-HER-targeted therapy, previous studies have shown that bispecific antibodies engineered from anti-EGFR or -HER2 may give promising results (19,20). Moreover, two-in-one antibodies, which created a surface that specifically binds two target antigens with high affinity using a single antibody binding site (21,22), have aroused abundant interest in the field.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro and in vivo tumor proliferation inhibition studies demonstrated that MBS301’s efficacy was obviously superior to that of T-mab or P-mab used alone. We found that the in vitro growth of trastuzumab-resistant HCC1419 cells was not affected by the addition of T-mab or P-mab alone; 20 however, growth was inhibited by the treatment with MBS301 or the combination of T-mab and P-mab. In MDA-MB-175VII, a HER2 low expression (HER2 oncoprotein 1+) breast cancer cell line, 21 the inhibition rate by MBS301 was 82.8%, slightly higher than others.…”
Section: Discussionmentioning
confidence: 83%
“…Because it was first identified as a family of possible oncogenes, the EGFR receptor family has been an attractive therapeutic target as these receptors are frequently upregulated in many cancers. Development of new HER2-targeted therapies, including antibody-delivered cytotoxins and chimeric antigenbased immune cell repertoires, has shown promise in both research and clinical settings (14,15,(30)(31)(32). However, while clinical targeting of EGFR function through small molecule inhibitors or antibody inhibition of EGFR signaling has shown some promise, successful long-term outcomes are rare because of compensatory kinase domain mutations or alternate receptor signaling and problems with toxicity to normal tissue (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%